Welfare-Enhancing Taxation and Price Discrimination - Anna D'Annunzio; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze the effects of commodity taxation in markets where suppliers implement second-degree price discrimination schemes, such as offering different package sizes and quality-differentiated versions of the same product. In these markets, suppliers distort the quantity (or quality) intended for all types of consumers, except for those with the highest marginal willingness to pay. We show that differentiated ad valorem taxes can alleviate this distortion, and thus increase government revenue as well as welfare, provided the tax rate increases with the size (or quality) of the good supplied.
Keywords: D40; H21; H22; L10; 330; commodity taxation; tax incidence; price discrimination